Komplexierung von 1,3-Dihydro-1,3-diborapentafulven-Derivaten mit Fe(CO)3-Fragmenten: Synthesen, Kristall- und Elektronenstruktur von μ-(η4:η5-1,3-Dihydro-1,3-diborapentafulven)-bis (tricarbonyleisen)-Komplexen - Feßenbecker, Achim; Enders, Markus; Pritzkow, Hans; Siebert, Walter; Hyla-Kryspin, Isabella; Gleiter, Rolf (Chemische Berichte - recueil, 1991)
Complexation of 1,3-Dihydro-1,3-diborapentafulvene Derivatives with Fe(CO)3 Fragments: Syntheses, Crystal and Electronic Structure of μ-(η4: η5-1,3-Dihydro-1,3-diborapentafulvene)-bis(tricarbonyliron) Complexes Reactions of the 1,3-diborapentafulvene derivatives 1a-c with (CO)3Fe(C8H14)2 lead to the violet dinuclear complexes 3a-c, which possess a slipped triple-decker structure. The X-ray structure analyses of 3b,c reveal that one Fe(CO)3 group is pentahapto-coordinated to the 1,3-diborole frame of C2B2C=C, whereas the other interacts with the Y-shaped B2C=C unit. The latter resembles the interaction of Fe(CO)3 with trimethylenemethane. An MO calculation indicates that the formation of 3 occurs by distortion of 1 · Fe(CO)3; the slippage of Fe(CO)3 from η5 to η4 bonding is followed by η5 coordination of the second Fe(CO)3 group.
Die Zahl "3" im Ausdruck "Fe(CO)3" ist tiefgestellt
First published: Juli 1991
Gesehen am 09.11.2022